The Relational God in the Presence of Evil: A Theology of Friendship - Sihombing, Hesron H. (2020)
The problem of suffering has been widely studied in Christian theology throughout history. This paper addresses suffering through a critical redefinition of God’spower manifested in the theological locus of friendship embodied in Jesus Christ. In the first part, I will redefine the meaning of God’s power and goodness as God’s relationality with creation. The second part will explore God’s relationality in Jesus as the participation of God in the suffering drawn from the concept of friendship. Keywords: Power, Suffering, Relationality, Friendship, Solidarity